Prevalence and Characterization of Streptococcus pyogenes Clinical Isolates from Different Hospitals and Clinics in Mansoura - Zeinab M. Helal; Dina E. Rizk; Mohamed M. Adel El-Sokkary; Ramadan Hassan (International Journal of Microbiology)
Streptococcus pyogenes are associated with many bacterial diseases in both humans and animals and are capable of causing a multitude of human diseases. S. pyogenes isolates were identified by their bacitracin sensitivity, positive spy1258 detection, and positive GAS latex agglutination. Different isolates were typed serotypically and genotypically by BOX-PCR. Different virulence factors were identified in S. pyogenes isolates. In addition, antimicrobial resistance was tested to eleven different antibiotics. Furthermore, the resistance mechanisms were determined phenotypically by the disc diffusion method. Finally, the correlation between both molecular and serotypes identified and the profile of virulence factors and clinical and geographical sources was determined for all isolates. Thirty-eight S. pyogenes isolates were collected from different clinical sources. Resistance testing indicated high resistance to mostly used antibiotics except amoxicillin/clavulanic acid, amoxicillin, and ampicillin. Serotyping results indicated five different serotypes, M1, M2, M3, M4, and M6, in S. pyogenes isolates, while six isolates were identified as untypeable. In addition, positive PCR results identified most of the tested SAgs genes in which speJ gene was mostly identified followed by speI, speC, and ssa genes being identified in 81.6%, 63.3%, 60.5%, and 60.5%, respectively. However, speH was the least detected. In contrast, speL, speM, and smeZ genes could not be detected in all tested isolates. Finally, BOX-PCR molecular typing was a more effective clustering method when compared to the serotyping method in all S. pyogenes. In conclusion, the isolates in this study were highly resistant to mostly used antibiotics. M1 was the most identified serotype. No significant association was found between serotypes, BOX-PCR cluster groups, and SAgs genes profiles. However, by the application of BOX-PCR, effective molecular typing was obtained.